Mecanismos de remoção de metais pesados em argila bentonita - Sallo, Fernando da Silva (2012)
One of the prominent global concerns is the quality of water available infountains, as the population and industrial growth has caused serious pollution in rivers and other water bodies. In this sense, several technologies have been proposed as a treatment of this water. The process investigated in this work is based on the sorption of heavy metals highly toxic ions Cd2+ Zn 2+ and Pb 2+, present in industrial, urban and mining wastewater. Among the sorbents available, excel up the clays. The Bofe bentonite clay is one of types of clays and is residual resulting from the extraction process Gypsum mining, hence it become low-cost material compared to other sorbents. When the bentonite clay is enrichedwith Ca2+, this material has acquired greater stability. From that, this dissertation aimed to investigate the basic mechanisms involved in the sorption ofcalcined BofeCa-bentonite clay via batch system.The ion exchange and adsorption mechanism was investigated as well as its predominance in removalof these metals at temperatures ranges of 20 to 50 °C. For this, B.E.T, XRD and TGA analyzes were carried out to characterize the material.Kinetic and sorption isotherms were obtained which itsdata were used for isothermaland kineticsmodeling, focusing on both adsorption and ion exchangeapproaches. In this context, the model of pseudo-second order kinetic responded better to the data while the isothermal process achieved good results with the Langmuir model. The ion exchange mechanism was predominant in terms of percentage removal for all metals studied. The sequence selectivity order obtained of Pb> Zn> Cd is linked to the electronegativity and hydrolysis constant of each metals. Moreover, it can be concluded that the Bofe Ca-bentonite clay is more efficient in removing the metals Pb, Zn andCd in aqueous solutions between temperatures 30 and 40 °C. This outcome was obtained by analysis of the thermodynamic properties,which were derived from isothermal models.